1994
DOI: 10.1002/ir.37019948204
|View full text |Cite
|
Sign up to set email alerts
|

Data, indicators, and the national center for higher education management systems

Abstract: To be useful for policy and decision making, indicators should be developed around sound conceptual frameworks and should encompass multiple aspects of institutional or system performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 2 publications
1
26
0
1
Order By: Relevance
“…Performance evaluation has become a major concern for colleges and universities (Ping, 1993;Serban, 1997;Burke and Serban, 1997;Burke, 1998). National commissions, federal and state governments, accrediting agencies, accounting standard setting bodies, and countless institutions that provide resources to colleges and universities are urging performance assessment (Banta and Borden, 1994;Ashworth, 1994;Ewell and Jones, 1994;Honan, 1995;Banta et al, 1996;Burke, 1998;Serban and Burke, 1998).…”
Section: A Public Accountability Framework For Higher Educationmentioning
confidence: 41%
“…Performance evaluation has become a major concern for colleges and universities (Ping, 1993;Serban, 1997;Burke and Serban, 1997;Burke, 1998). National commissions, federal and state governments, accrediting agencies, accounting standard setting bodies, and countless institutions that provide resources to colleges and universities are urging performance assessment (Banta and Borden, 1994;Ashworth, 1994;Ewell and Jones, 1994;Honan, 1995;Banta et al, 1996;Burke, 1998;Serban and Burke, 1998).…”
Section: A Public Accountability Framework For Higher Educationmentioning
confidence: 41%
“…This is well supported in the literature, where faculty practices such as active learning and higher-order cognitive activities create environments that positively relate to student engagement (Chickering and Gamson 1987; Ewell and Jones 1996; Kumbach and Wawrzynski 2005; Tinto 1993, 2000). Additionally, we found that students tend to be more engaged when professors create an atmosphere where inquiry is valued and no question is too elementary.…”
Section: Resultsmentioning
confidence: 68%
“…Many scholars, including Chickering and Gamson (1987), Ewell and Jones (1996), and Tinto (1993, 2000), have documented the strong association between faculty-student interactions and increased student learning and engagement. Students often arrive at college not knowing whom or how to ask for help, and faculty shape the climate and classroom activities that orient students in ways that affect their likelihood of success.…”
Section: The Importance Of Academic Engagementmentioning
confidence: 99%
“…General institution-wide support for emphasizing student success and service to the community is undermined by the perception of staff that they are already working toward these goals on their own. Although individuals and their units often make extra efforts to assist students and other campus visitors and constantly look for ways to improve the services they provide, the various units of the campus are unable or unwilling to work collectively (Ewell, 1996). The apparent lack of effective cross-unit communication was first identified in the 1987 accreditation review and continues to be an issue at the college.…”
Section: Systemic Problemsmentioning
confidence: 99%